Modifikasi Tata Rias Pengantin dalam Upacara Pernikahan Adat di Kecamatan Kumun Debai Kabupaten Kerinci. - Herman, Silvia; Rahmiati, Rahmiati; Yanita, Merita (Journal of Home Economics and Tourism, 2016)
Nowdays make up bridal in Indonesia has undergone many changes and modification. As a result the value in culture have started to fade meanwhile the new value has not formed steady basis yet. In the growth of the make up bridal in Kumun Debai also getting influence by development of the modern world. This research aims to know makeup and bridal hair styling, look at the changes that occur between the traditional wedding dress and modification, and express the meaning / philosophy of wedding dress in the District Kumun Debai Kerinci. The method used in this research is qualitative method with a naturalistic approach, where reseacher observe object naturally in the field. Instrument used by researcher is the researcher it self. While the technique of data collection for this research using the technique of interviewing, observation, documentation and complication of these three technique. To get the result of the research, data such be reduced first then made the last presentation of the data and drawing conclusion. The result showed the changes occuring in the make up, hair styling and traditional wedding dress. Make up and hair on the Kumun Debai bride both past and present is valid only for the bride while the groom looks like everyday. Fomerly the bride’s make up is quite simple compared to the bride’s make up right now. Now days the bride’s make up more complex and rather complicated. Hair styling the bride formerly using one of braided cemara as for. But today very rare bride who does not use head scraff in Kumun Debai. Traditional wedding dress for the groom and the bride in Kumun Debai both are modified on shaped, models, and colors. Although the wedding dress has changed but the meaning and philosophy which is contained on it always tried to maintain it.   Keyword: modification make up bridal, traditional wedding dress.